Preparing parents for parenthood: protocol for a randomized controlled trial of a preventative parenting intervention for expectant parents - Mandy Mihelic; Alina Morawska; Ania Filus (BMC, 2018)
Abstract Background Becoming the parent of a new baby comes with a range of challenges including difficulties with emotional adjustment, couple relationship issues and difficulty managing common infant behaviors, such as crying and sleep problems. This time can be especially challenging for couples who experience a range of risk factors. Previous parenting interventions for parents of babies have shown mixed results. This protocol paper describes a randomized controlled trial of a group-based parenting intervention for high-risk parents expecting their first baby. Methods/design Participants will be randomized to either Group Baby Triple P or Care as Usual (CAU). Group Baby Triple P involves 4 × 2 h group sessions delivered during pregnancy and 4 individual telephone sessions of 30 min each in the early postnatal period. Outcomes will be assessed via parent self-report questionnaire, home observations and a baby diary 10 weeks and 6 months post-birth. Primary outcomes will be parental confidence and perceived competence. Secondary outcomes will include parental responsiveness and bonding with the baby, relationship happiness, life satisfaction, depression, anxiety and stress, and infant crying and sleep. Analyses will involve a series of rANOVA and rMANOVAs, t-tests and a multilevel modeling approach. Discussion A brief summary, strengths and potential implications are discussed. Trial registration Australian New Zealand Clinical Trials Registry: ANZCTR 12613000948796. Registered 27 August, 2013.